Literature Review: Factors Related to Menopause - Risti Marliani; Miftahul Jannah; Siti Umi Nur Almi sarina; Siti Zulaiha; Titin Indriany; Luvi Dian Afriyani (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Menopause is a natural phase in a woman's life characterized by the permanent cessation of menstruation due to a decline in estrogen hormone levels. biological factors (age at menarche, parity, hormonal contraception), social factors (work, education), and lifestyle factors (physical activity and diet). Although it is a natural process that inevitably occurs, the age of menopause onset and the intensity of symptoms that accompany it show very significant variation between individuals. This study aims to identify, analyze, and construct various multidimensional factors that trigger the acceleration of the age of menopause onset and affect the severity of symptoms experienced by women during the transition period. This study used a literature review method by searching for articles through the Google Scholar and PubMed databases from 2018 to 2025. The articles included were full-text articles with quantitative and qualitative research designs using the PICO (Population, Intervention, Comparison, Outcome) approach. Of the twenty articles identified, ten met the inclusion criteria. The results show that factors influencing menopause include biological factors (age at menarche, parity, hormonal contraception), social factors (occupation, education), and lifestyle factors (physical activity and diet). Six journals discuss the age of first menstruation, four journals discuss parity, three journals discuss hormonal birth control, one journal discusses education, lifestyle. Factors that can influence the incidence of menopause for women in Indonesia are characteristic factors consisting of biological factors (age at menarche, parity, hormonal contraception), social factors (work, education), and lifestyle factors (physical activity and diet.